Deep Breathing Exercise For Decreasing Anxiety Level on People Undergo Covid 19 Vaccination - Dwi Rahayu; Hengky Irawan; Puguh Santoso (STIKES Karya Husada Kediri, 2022)
Everyone during the current pandemic lives in a fairly high level of uncertainty. The situation in the pandemic changes at any time, the government's recommendations go up and down. The government's plan for a COVID-19 vaccine for the entire population of Indonesia has generated various responses in the community. The number of notifications that come from many sources can affect people's perceptions of vaccines. The negative perception of vaccines experienced by the community can trigger anxiety. Deep Breathing Exercise is one of the non-pharmacological treatments which is an effective method to reduce anxiety. The purpose of this study was to determine the effectiveness of deep breathing exercise on reducing anxiety levels in clients who will undergo covid 19 vaccination at the Kediri City Police. The research design used was a pre-experimental design with a one-group pretest-posttest design. Respondents in this study were 50 respondents. The sampling technique used is purposive sampling, data collection using a questionnaire sheet and interviews using the HARS scale. The results showed that the pretest data for Deep Breathing Exercise were 2 people with severe anxiety (4%), moderate anxiety 25 people (50%), mild anxiety 23 people (46%). Posttest Deep Breathing Exercise patients with severe anxiety 0 people (0%), moderate anxiety 11 people (22%), mild anxiety 12 people (24%) and 27 (54%) not anxious. Based on the results of research analysis using the Wilcoxon Sign Rank Test, the results showed that p-value: 0.000 < 0.05. There is an effect of Deep Breathing Exercise on the level of anxiety in clients who will undergo the covid 19 vaccination. Recommendations for further researchers are expected to use more samples and more homogeneous treatment. So that it will have a greater effect on decreasing the client's level of anxiety. Keywords: Deep Breathing Exercise, level of Anxiety, Covid 19 Vaccination